Ketersediaan Pangan Beras di Kabupaten Padang Pariaman - Afrina, Lusi; Wilis, Ratna (Lembaga Yasin AlSys, 2023)
This research aims to determine the convergence of rice fields in Padang Pariaman Regency, to determine the carrying capacity of rice fields in Padang Pariaman Regency, and to determine the availability of rice in Padang Pariaman Regency. The method used is a quantitative method with quantitative descriptive analysis. The results of this research are Kab. Padang Pariaman experienced land conversion from 2013 until now, which has an impact on the carrying capacity of land and rice production or the availability of rice in Padang Pariaman. The amount of rice availability in the Padang Pariaman area shows that rice production and rice availability have continued to decline in the last five years, namely in 2018 rice production reached 280,892 tons, then fell to 227,996 tons in 2022. Likewise, the availability of rice produced decreased in 2018 179,766.56 tons then in 2022 it will become 145,913.12 tons. However, even though production continues to decline in the Kab. Padang Pariaman still has a rice surplus value, meaning that the amount of rice available is greater than the amount of food/rice requirements or in this case it is still in the balanced category.